Tennis at tiebreaks: addressing elite players` performance for tomorrows` coaching - Meffert, D.; O`Shannessy, C.; Born, P.; Grambow, R.; Vogt, T. (German Journal of Exercise and Sport Research, 2019)
The tiebreak in tennis is one of the most-contested situations during a set. Often the outcome of a tiebreak is trendsetting for the match. Thus, every point in a tiebreak may be defined as a "big point", and only the best players are able to play their best tennis. However, differences in players` performances between tiebreak points (TBP) and non-tiebreak points (NTBP) remain to be elucidated. Therefore, this study aimed to compare players` performance at TBP and NTBP. For this, the rally length, serve and return behaviour, as well as the number of winners and forced and unforced errors for male players in the Wimbledon tournament 2016 were examined to determine possible impacts of a supposable mental stress in the tiebreak situation. A total of 28,570 points were analysed and divided into TBP (n?=?1039) and NTBP (n = 27,531). It was shown that rally length increases subsequent to the first serve (p < 0.1; 3.27 to 3.70 shots) and that players produce less unforced errors at tiebreaks (p < 0.1; 23.50 to 20.60%). Further research may investigate a potential impact of these findings on winning or losing a tiebreak, eventually indicating future practice patterns that explicitly consider mental skills situations. Der Ausgang eines sog. Tiebreaks, der einen der engsten Momente eines Satzes darstellt, ist oft richtungsweisend für den weiteren Verlauf eines Matches. Dementsprechend ist jeder gespielte Punkt während eines Tiebreaks ein wichtiger Punkt und nur den besten Spielern gelingt es, in dieser Situation ihr bestes Tennis abzuliefern. Da dieser Leistungsunterschied zwischen Tiebreak-Punkten (TBP) und normalen Punkten (NTBP) bisher nicht geklärt wurde, untersucht diese Studie die Leistungen von Profitennisspielern während des Herren-Tennisturniers von Wimbledon 2016 in Bezug auf die Ballwechsellänge, das Aufschlagverhalten, die Anzahl von gespielten Fehlern ("unforced" und "forced errors") sowie die Anzahl von direkten Gewinnschlägen. Die Untersuchung von insgesamt 28.570 Punkten (NTBP n=27.531, TBP n=1039) hat neben einer Verlängerung der Ballwechsellänge nach dem ersten Aufschlag (p < 0,1; 3,27 zu 3,70 Schläge pro Ballwechsel) u.a. auch eine Reduzierung der "unforced errors" bei Tiebreaks (p < 0,1; 23,50% zu 20,60%) ergeben. Die Frage, welchen Einfluss diese Erkenntnisse auf den Ausgang eines Tiebreaks haben, sowie die Erarbeitung verschiedener Herangehensweisen in mentalen Drucksituationen sollten im Mittelpunkt zukünftiger Untersuchungen stehen.